The Use of Fatimah Grass Among Young Mothers in North Sumatera - Muhammad Faiz Sultan; Fotarisman Zaluchu; Putri Grace Kelly Tuanakotta Tuanakotta; Nanda Cyntia Dewi; , Nur Ulia L. Gaol; Chandra Tanuwijaya; Zhafira Kamila (Talenta Publisher, 2023)
mothers in the community. This study uses a qualitative approach with ethnographic research design, which involves in-depth interviews, participatory observation, and documentation studies. The main respondents in this study were young mothers aged 18-40 years who used Fatimah Grass as part of their traditional medicine or health support. The results showed that Fatimah Grass still has an important role in the daily lives of young mothers in the community. Fatimah grass is used by young mothers for various purposes, such as improving reproductive health, postpartum recovery, and increasing milk production. The use of Fatimah Grass by young mothers is also related to tradition, knowledge passed down from generation to generation, as well as perceptions of the safety and effectiveness of the plant. Social factors, including family support and influences from the surrounding community, also influence the use of Fatimah Grass by young mothers.